Human papillomavirus and cervical neoplasia: scientific production of the countries of Latin America and Caribbean in last 11 years - Guanilo, Mónica Cecilia TU; Moura, Roudom F; Conceição, Crizelide A; Nichiata, Lucia YI (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction:since 1995 papillomavirus has been associated with cancer of the cervix. In the world, approximately 37 thousand deaths have beenreported due to cancer of the cervix, with papillomavirus being prevalent in 99.7% of these women. Colombia, Argentina and Jamaica are countriesof Latin America and the Caribbean with the highest prevalence. Objectives:to describe the scientific production of Latin American and Caribbeancountries that describes the association between papillomavirus and cervical cancer in order to identify the gaps of knowledge in this scientific pro-duction. Methods:a review of the literature was conducted from 1995 to 2005 in the LILACS database using the following key words: Cervix Neo-plasia, Papillomavirusand Papillomavirus Infections. The abstracts were analyzed and organized by year of publication, authors ́ country, publica-tion language and subject. Results:a total of 22 abstracts were analyzed; most of the scientific production was published in the last four years; Brazil,Mexico, Cuba and Chile were the countries with the largest number of publications, and the English language predominated. The studies mainly dealtwith the clinical and epidemiological aspects of the association between Papillomavirus and cervical cancer. The author identified the need for scien-tific production that will analyze the situation with emphasis on gender, vulnerability and social insertion, as well as studies exploring new mannersor techniques for the acquisition of the knowledge about the prevention of Human Papillomavirus and cervical cancer, so that women will acquiremore autonomy regarding their own health. Conclusion: despite the scientific production that has subsidized programs of cervical cancer prevention,the expected impact has not been reached. Even with the production of a vaccine against Papillomavírus, it is necessary to carry out new studiesaiming at greater autonomy for women. It is necessary to intensify scientific production in order to develop theories and methods that will clarify therelationship between the development of the illness in women and concrete forms of intervention.